Mercury Is Taken Up Selectively by Cells Involved in Joint, Bone, and Connective Tissue Disorders - Pamphlett, Roger; Kum Jew, Stephen (Frontiers in Medicine, 2019)
Background: The causes of most arthropathies, osteoarthritis and connective tissue disorders remain unknown, but exposure to toxic metals could play a part in their pathogenesis. Human exposure to mercury is common, so to determine whether mercury could be affecting joints, bones and connective tissues we used a histochemical method to determine the cellular uptake of mercury in mice. Whole neonatal mice were examined since this allowed histological assessment of mercury in joint, bone and connective tissue cells. Materials and methods: Pregnant mice were exposed to a nontoxic dose of 0.5 mg/m3 of mercury vapor for 4 hours a day on gestational days 14 – 18. Neonates were sacrificed at postnatal day 1, fixed in formalin, and transverse blocks of the body were processed for paraffin embedding. Seven micrometer sections were stained for inorganic mercury using silver nitrate autometallography, either alone or combined with CD44 immunostaining to detect progenitor cells. Control neonates were not exposed to mercury during gestation. Results: Uptake of mercury was marked in synovial cells, articular chondrocytes, and periosteal and tracheal cartilage cells. Mercury was seen in fibroblasts in the dermis, aorta, esophagus and striated muscle, some of which were CD44-positive progenitor cells, and in the endothelial cells of small blood vessels. Mercury was also present in renal tubules and liver periportal cells. Conclusions: Mercury is taken up selectively by cells that are predominantly affected in rheumatoid arthritis and osteoarthritis. In addition, fibroblasts in several organs often involved in multisystem connective tissue disorders take up mercury. Mercury provokes the autoimmune, inflammatory, genetic and epigenetic changes that have been described in a range of arthropathies and bone and connective tissue disorders. These findings support the hypothesis that mercury exposure could trigger some of these disorders, particularly in people with a genetic susceptibility to autoimmunity.